Relationships between cagA, vacA, and iceA genotypes of Helicobacter pylori and DNA damage in the gastric mucosa - Ladeira, MSP; Rodrigues, MAM; Salvadori, Daisy Maria Favero [UNESP]; Neto, P. P.; Achilles, P.; Lerco, Mauro Masson [UNESP]; Rodrigues, Paulo Antônio [UNESP]; Goncalves, I; Queiroz, DMM; Freire-Maia, D. V. (Wiley-Blackwell, 2004)
Helicobacter pylori (H. pylori) is believed to dispose carriers to gastric cancer by inducing chronic inflammation. The inflammatory processes may result in the generation of reactive oxygen and nitrogen species that damage DNA. In this study, we investigated the relationships between DNA damage in the gastric mucosa and cogA, vocA, and iceA genotypes of H. pylori. The study was conducted with biopsies from the gastric antrum and corpus of 98 H. pylori-infected and 26 uninfected control patients. H. pylori genotypes were determined by PCR and DNA damage was measured in gastric mucosal cells by the Comet assay (single cell gel electrophoresis). All patients were nonsmokers, not abusing alcohol, and not using prescription or recreational drugs. Levels of DNA damage were significantly higher (P < 0.0001) in the H. pylori-infected patients than in uninfected patients. In comparison with the level of DNA damage in the uninfected controls, the extent of DNA damage in both the antrum (OR = 8.45; 95% Cl 2.33-37.72) and the corpus (OR 6.55; 95% Cl 2.52-17.72) was related to infection by cagA(+)/vocAs1m1 and iceA1 strains. The results indicate that the genotype of H. pylori is related to the amount of DNA damage in the gastric mucosa. These genotypes could serve as biomarkers for the risk of extensive DNA damage and possibly gastric cancer. (C) 2004 Wiley-Liss, Inc.
Keywords: Helicobacter pylori; genotypes; DNA damage; comet assay